Biostimulants promote the accumulation of carbohydrates and biosynthesis of anthocyanins in ‘Yinhongli’ plum - Yao, Lu; Liang, Dong; Xia, Hui; Pang, Yazhuo; Xiao, Qiao; Huang, Yan; Zhang, Wen; Pu, Changbing; Wang, Jin; Lv, Xiulan (Frontiers in Plant Science, 2023)
Biostimulants play an important role in promoting crop growth and development, and improving fruit yield, but their influence on fruit quality on horticulture plant is still unclear. In this study, four type of biostimulants (Ainuo, Aigefu, Weiguo, and Guanwu Shuang) were applied to fruit surface of ‘Yinhongli’ plum to investigate their effect on fruit quality. Results showed that all biostimulant treatments significantly improved total soluble sugar content in fruit, and the expression level of genes related to sugar metabolism. In addition, WG and GS treatments significantly increased the expression of structural genes involved in anthocyanin biosynthesis compared with the control, especially CHS and UFGT at 95-105 d after anthesis, leading to anthocyanin accumulation 10 days earlier than the control. Correlation analysis showed that there was a significant correlation between total sugar and anthocyanin content during fruit coloring and ripening.